Metallic tin substitution of organic lead perovskite films for efficient solar cells. Issue 41 (10th October 2018) - Zhao, Jinjin; Wei, Liyu; Jia, Chunmei; Tang, Hao; Su, Xiao; Ou, Yun; Liu, Zhenghao; Wang, Chen; Zhao, Xingyu; Jin, Hongyun; Wang, Peng; Yu, Gang; et al.
Abstract : Low-leaded perovskite solar cells are operated using inorganic active metal substitution of lesser active organometal halide perovskite. Abstract : Perovskite solar cells are promising highly efficient and low-cost photovoltaic devices. Nevertheless, the use of the toxic element Pb is still a big challenge for the mass production of highly efficient perovskite solar cells. In this work, a novel and facile technique is presented to fabricate tin-lead alloyed perovskite films using metal precursors and a substitution method. Herein, the perovskite films are formed as a result of the substitution reaction between the Sn metal precursor and methylammonium triiodideplumbate (CH3 NH3 PbI3, MAPbI3 ) solution carried out at 70 °C. The maximum Sn content in perovskite films reaches up to 15% with a substitution reaction time period of 1 day. Through this substitution technique and the unique growth mechanism, a less-toxic and efficient perovskite solar cell with a power conversion efficiency (PCE) of 12.46% is fabricated. It is found that this substituting strategy can exploit a new direction to further explore different active metals substituting less active organic metallic systems with even lower temperature conditions.